Perceptions of Prospective Ire Teachers in the IPAI Study Program at UPI Regarding the Future Careers of Islamic Education Teachers in the Modern Era - Rosmayati Rosmayati; Syahidin Syahidin; Agus Fakhruddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The modern era has brought significant changes to the world of education. Teachers are the forefront of changing social dynamics, as they are required to possess comprehensive competencies in facing modern developments and progressive social dynamics. This should be used as a study material in building positive perceptions of prospective professional teachers in facing the dynamics of modern society, especially prospective Islamic Religious Education (IRE) teachers. This study aims to describe and analyze the perceptions of prospective Islamic Religious Education (IRE) students in the UPI Science and Islamic Studies Study Program regarding the future careers of IRE teachers in the modern era. This type of research is quantitative descriptive with convenience sampling technique. Data collection was in the form of a Likert-scale questionnaire on IPAI students class of 2022-2023. This study used statistical tools in the form of average value, standard deviation, minimum value, and maximum value. The results of the study revealed that the perception of prospective Islamic Education teacher students in terms of the competency standards that teachers must have, namely: pedagogical competence, there are 68% of student perceptions of Very High, personality competence 69% in the same category, social competence 66%, professional competence 71% and one specific competency for Islamic Education teachers, namely religious competence, at 67%. Thus, this study recommends that the IPAI UPI Study Program can ensure the readiness of prospective Islamic Education teacher students to become competent and professional teachers.